The Students' Perception on the Use of Picture to Improve Descriptive Paragraph Writing at Christian University of Indonesia - Pasaribu, Elisa Tumiar (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2017)
AbstractThe objectives of this study were to examine the students’ perception on the use of picture in writing descriptive paragraph and to investigate whether the students were interested in the use of picture in writing descriptive paragraph. This study was a survey using the qualitative and survey design. It involved 34 students of English Teaching Study Program, Christian University of Indonesia. To achieve the objectives, qualitative and quantitative data concerning the students’ perceptions and interest were collected through a questionnaire and interview. The survey was administered to the eight semester students of 2012/2013 academic year. To support this research the data obtained through the open ended questionnaire, interview was conducted toward four students. The quantitative data were analyzed by using Microsoft Excel 2007, while the qualitative data were analyzed descriptively. The result of this study indicated that almost all of the students agreed to use the picture in developing their descriptive paragraph writing. The use of picture in writing also helped them understand the descriptive paragraphs even though they knew there was another media, i.g. realia, which could help them write a descriptive paragraph. Thus it is sugested that the English teachers should use this technique to improve students’ descriptive paragraph writing. Keywords: perception, picture, writing, descriptive paragraph